SYSTEMATIC LITERATURE REVIEW: MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERHADAP MOTIVASI BELAJAR MATEMATIKA DI SEKOLAH MENENGAH - Novianti, Irhaz (UNIVERSITAS TANJUNGPURA, 2024)
Mathematics holds a significant role in the world of education and can foster critical thinking, logical reasoning, and problem-solving abilities. However, many students harbor negative perceptions about mathematics, hindering their learning motivation. To minimize these negative attitudes, there is a need for innovative approaches to mathematics instruction that involve active student engagement. The Teams Games Tournament cooperative learning model is one such approach that can be implemented. This research aims to review the literature on the application of the Teams Games Tournament model in enhancing students' learning motivation in mathematics. This research uses a Systematic Literature Review methodology, which entailed searching for relevant research articles through google scholar. The search criteria considered publication year, educational level, learning model, research methods, and the variables investigated. From this process, 16 articles were chosen according to the inclusion and exclusion criteria. The findings of this research indicate that the Teams Games Tournament learning model positively influences students